Anomalous Origin of Left Coronary Arteries From the Pulmonary Artery (ALCAPA) in an Asymptomatic 28-Year-Old Female. (21st September 2018) - Al Shaarani, Majd; Alzubaidi, Yasir; Jin, Long
Abstract: The anomalous origin of the coronary arteries is a rare finding that requires surgical correction. The most common anomaly in this group is the anomalous left coronary artery from the pulmonary artery (ALCAPA). The incidence of ALCAPA ranges between 1 and 8 in 100, 000 live births. This condition is usually discovered in the very first few days to months of life and can be fatal if not corrected surgically, with a mortality rate between 80% and 90%. Only rarely do patients with ALCAPA reach adulthood without symptoms. We report a case of anomalous origin of left coronary artery (ALCAPA) in a 28-year-old African American female. This very rare case was discovered during forensic autopsy. The deceased was apparently healthy and asymptomatic since she was at work when she suddenly collapsed. At the autopsy, the examination of the cardiovascular system revealed a 370-g heart. Transverse and longitudinal dissection of the coronary artery system revealed an anomalous origin of the left main coronary artery from the pulmonary artery. The lumina of the left anterior descending and left circumflex arteries were significantly smaller than the usual size. A single coronary ostium was present in the aortic root with higher than usual takeoff location (10 mm from the sinotubular junction). The myocardium of the left ventricle was 1.3 cm in thickness with focal fibrosis at the anterolateral free wall measuring 2 cm in the maximal dimension. Microscopically, the sections from the anterolateral wall of the left ventricle revealed patchy myocardial fibrosis more prominent at the papillary muscle and subendocardium corresponding with remote myocardial ischemic injury. The sections also revealed subtle changes consistent with acute ischemic injury, including eosinophilia, few neutrophils, shrunken pyknotic nuclei, and contraction band necrosis. There were areas of hypertrophic cardiomyopathy with boxcar-shaped nuclei.